Execution Time of Quick Sort on Different C Compilers: A Benchmark - Kaur, Mehzabeen; Jangra, Surender (International Journal of Computer Sciences and Engineering, 2025)
Sorting is a process of arranging the elements in specific order. Computer systems use many sorting algorithms to arrange the numbers in ascending or descending order and ‘quicksort’ is one of the better performing algorithms. This algorithm follows divide-and-conquer approach by compiling the large data set to partition the list of elements and then exchange the numbers after scanning the list. In today’s ever expanding world of technology, users find themselves in a situation where they have so many choices in selecting the best compilers. However, most of the time, technically the users are not able to identifying which translator is the best one for the completion of a particular assignment. The main aim of this paper is to find out the best compiler for ‘quick sort’ to reduce the execution time and automation through analyzing the performance of different compilers